Exploration of the potential of vitamin premix with different doses to increase growth and survival of saline tilapia (Oreochromis niloticus) on laboratory scale environment - Hasim Hasim; Salma Suna; Rully Tuiyo (Gorontalo State University, 2022)
Tilapia is an important commodity for Indonesian fisheries. Therefore, tilapia cultivation continues to grow. The goal is to meet market needs and increase production more optimally. One of them is through feed innovation to increase growth and maximum survival. This study aimed to explore the effect of giving vitamin premix with different doses on the growth and survival of saline tilapia (Oreochromis niloticus) fry. The method used is an experiment with a completely randomized design (CRD) which consists of 4 treatments with three replications. Treatment A (without added vitamins), B (vitamin premix 3%), C (vitamin premix 4%), D (vitamin premix 5%). The results showed that treatment D had a significant effect on increasing the weight and length of saline tilapia with an average weight value of 3.21 and an average length value of 2.67, followed by treatment C weight with a value of 2.50 and a length of 2, 05, treatment B was heavy with a value of 2.49, and length of 1.86 and treatment A was heavy with a value of 1.60, and length of 1.23. The highest survival was in treatment D with a value of 100%, treatment C with a value of 93.3%, treatment B with 86.7%, and treatment A with 80.0%. Vitamin premix dose D gave the best effect, so it has the potential to be applied in saline tilapia cultivation.